PREDIKSI PERMINTAAN DAN PERSEDIAAN DARAH : PENDEKATAN DENGAN METODE DOUBLE EXPONENTIAL SMOOTHING - Batarius, Patrisius; Sinlae, Alfry Aristo Jansen (Universitas Nusa Cendana, 2024)
There is a daily blood transfusion in the hospital. Blood management and distribution systems have been integrated into each UTD-PMI. Different systems were formed to maintain a balance between the demand and supply of blood bags. UTD-PMI Kota Kupang serves blood requests in 12 hospitals and 1 clinic located in the city and Kupang district. The demand for more blood than the supply of blood in the UTD-PMI is a personal problem. The prediction of demand and the blood supply becomes important so that there is no difference in demand and supply of blood in the very large UTD-PMI office. The study used the Double Exponential Smoothing (DES) method to predict blood supply and demand. Data from the last four years is used to predict the amount of blood demand and supply. Predictions with the DES method are divided into two categories. The first category uses the data of the last 3 years to predict data in the fourth year for the next 6 months. The training data used is divided into two types: the last 3 years and the last 2 years. Forecast results compared to real data in 2023. Category 2 uses data from the last four years to predict data for 2023. The training data used is divided into 4 types, each starting from the last 4, 3, 2, and 1 year. To determine the accuracy of the calculation using the mean absolute percentage error (MAPE). The results of determining training data with different ranges result in predictions of blood demand and blood supply, whose results are also different but still in the “good forecast” category.